REAL-WORLD PBL IN AN ENGLISH BOOTCAMP: ENHANCING ENGINEERING STUDENTS’ LEARNER AUTONOMY - Saad, Sharina; Zolkifli, Alia Nabella Fateha (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
Short-term intensive English language programmes are frequently used to strengthen learners' communication confidence; however, limited empirical attention has examined whether short-duration immersion programmes can foster learner autonomy among engineering undergraduates in Malaysian higher education, particularly when organised through problem-based learning (PBL). Anchored in learner autonomy theory, self-directed learning, and constructivist principles of PBL, this study examined autonomy-related learning behaviours among Malaysian engineering students who participated in a three-day English Language Bootcamp Immersive Program. A mixed-method post-program design was employed with 37 participants. Quantitative data were collected through five-point Likert-scale items measuring control, decision-making, ownership, choice, goal setting, independent learning, creativity, and problem-solving, while qualitative data were gathered through open-ended responses. Descriptive statistics, Cronbach's alpha, and thematic coding were used to analyse the data. The findings indicated relatively high levels of learner autonomy, with a composite mean score of 3.88 (SD = 0.69), supported by strong internal consistency for the learner autonomy scale (alpha = .92). Independent learning and goal setting emerged as the most strongly endorsed autonomy dimensions. Qualitative findings further highlighted engagement, language development, collaboration, and students' desire for more speaking practice. The study demonstrates that short-term PBL-based immersive programmes can serve as effective pedagogical interventions for fostering learner autonomy, collaborative engagement, and self-directed learning in ESL contexts. The findings offer practical implications for designing intensive language immersion programmes in higher education.